Mental Health Analysis with Artificial Intelligence - Shalini Verma,; Shruti Sharma,; Dr. Pardeep Arora, (International Journal of Scientific Research in Science and Technology, 2025)
This dissertation explores the role of AI technologies in modern mental healthcare and reviews recent developments achieved by researchers, with a special focus on the growing field of digital psychiatry. Furthermore, it delves into the ethical challenges associated with the expanding influence of artificial intelligence in mental healthcare. Mental health-related illnesses are considered one of the most significant global challenges, impacting millions of individuals worldwide and contributing to high rates of disability.Artificial intelligence is revolutionizing mental healthcare through its applications in computational psychiatry, which harnesses quantitative methods to enhance the understanding, diagnosis, and treatment of mental illnesses. Well-designed Artificial Intelligence (AI) has proven to be a hidden advantage for many, enhancing diagnostic accuracy, promoting personalized therapy, and expanding access to mental health services. AI has introduced innovative solutions by improving mental health assessments, tailoring interventions, and increasing accessibility. It utilizes various tools, including machine learning algorithms, AI-powered chatbots, and wearable devices, for mental health diagnosis, therapy, and monitoring. However, ethical concerns surrounding these tools, along with challenges such as insufficient user engagement and poor integration into existing healthcare systems, continue to persist.